FAKTA KASUS KEKERASAN DALAM RUMAH TANGGA (KDRT) DI DEPOK SUAMI DAN ISTRI SAMA-SAMA JADI TERSANGKA TAPI HANYA ISTRI YANG DITAHAN ANALISIS WACANA KRITIS MODEL SARA MILLS - Nurul Hasan; Agus Hamdani (MATAPENA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2023)
Domestic violence refers to various physical, emotional, psychological, or sexual actions carried out by one family member against another within the household or domestic relationship. The author employs a descriptive analysis method in this research. The data source for this study is an article titled "Fakta Kasus KDRT di Depok: Suami dan Istri Sama-sama Jadi Tersangka, tapi Hanya Istri yang Ditahan" ("Facts of Domestic Violence Case in Depok: Both Husband and Wife Become Suspects, but Only the Wife Is Detained"). Data collection is conducted as follows: (1) Thoroughly reading the violence case news to gain an overview and understanding of the presented news content. (2) Identifying data related to women in the domestic violence case news using the perspectives of the subject's position, object's position, and reader's position. (3) Analyzing data indicating domestic violence cases against women from the perspectives of the subject's position, object's position, and reader's position. (4) Interpreting data on domestic violence cases against women using the perspectives of the subject's position, object's position, and reader's position. (5) Drawing conclusions from the research results. Women are portrayed as subjects, not objects of exploitation. Meanwhile, the object in the text is her husband/the actor committing violence. The reader, as the subject, is shaped by the reporting (ideological subject), accepting it as a reality. The author's suggestions include paying attention to up-to-date information and determining society's stance towards the violence experienced by women in the presented news. Keywords: Sara Mills, Critical Discourse, Online News.